Pent-up demand for surgery in the Manaus metropolitan region: A population-based cross-sectional study. Issue 31 (August 2017) - Ferreira, Priscila Gusmão da Silva; Galvao, Tais Freire; Silva, Marcus Tolentino
Abstract : Abstract: Waiting lines in healthcare reflect an imbalance between the availability and the demand for medical services. This study aimed to analyze the prevalence and factors associated with the pent-up demand for surgical procedures in the Manaus metropolitan region. We performed a population-based cross-sectional study in 2015. Pent-up demand was based on self-report by the participants; those who reported waiting were contacted by phone to clarify the nature and reasons for the experienced delay. We interviewed 4001 adults in their households. The pent-up demand for surgical procedures in the Manaus metropolitan region was 14% (95% confidence interval: 13-15%). The surgical specialties with the highest demand included orthopedics (18.1%), gynecology (17.0%), ophthalmology (12.4%), neurosurgery (10.8%), and general surgery (10.2%). The main reason for not accessing services was their lack of availability in the public health system, leading some patients to pay for procedures in private facilities. The populations most affected by pent-up demand included elderly individuals, women, and housewives. Pent-up demand for surgical procedures is a common problem in the Manaus metropolitan region and thus requires coordinated actions to optimize access to and capacity of the healthcare system.